Analysis of Digital Transformation in Islamic Finance with AI: A Sustainable Development Perspective - Rosidawaty; Ingkak Chintya Wangsih (www.amertainstitute.com, 2025)
Digital transformation in Islamic finance is crucial for supporting sustainable economic growth and achieving global development goals. AI can help make the Islamic financial system more efficient, transparent, and inclusive. However, the adoption of this technology still faces numerous challenges. These include the technology's readiness, the existence of applicable regulations, and the extent of public acceptance. This study examines how artificial intelligence contributes to the Sustainable Development Goals (SDGs) in the digital transformation of Islamic finance. This research was conducted using a qualitative approach through a literature review and analysis of secondary data from industry reports, journals, and related publications. The results show that artificial intelligence strengthens Islamic finance, particularly through more efficient and transparent management of zakat, waqf, and Sharia-compliant investments. Furthermore, the application of artificial intelligence has the potential to promote financial inclusion by reaching communities previously excluded from formal financial services. The study concludes that AI-based digital transformation in Islamic finance not only improves the efficiency of the financial system but also contributes to the achievement of the SDGs, particularly in poverty alleviation, social inclusion, and economic sustainability. Recommendations are provided for the development of regulations and policies to support the optimal adoption of this technology.